Association of self-reported craniocerebral trauma with re-offending: a cross-sectional survey among prisoners and detainees - Ya'nan LUO; Yantao WANG; Xiaoping WU; Jing ZHANG; Xiangwei GE; Wenxia AN; Chenlu HONG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the relationship between craniocerebral trauma and the risk of recidivism among prisoners. MethodsWith multi-stage equidistant sampling and the Re-Offending Questionnaire developed by domestic researchers, a face-to-face survey was conducted among 8 417 prisoners and detainees in 78 prisons, juvenile correctional facilities or community correction centres in 13 provinces and municipalities in China during August - December 2019. The relationship between the history of craniocerebral trauma and recidivism was analyzed using Chi-square test and logistic regression model. ResultsTotally 7 502 participants with complete information were included in the analysis. Craniocerebral trauma history was reported by 14.90% of 4 483 re-offenders and the ratio was significantly higher than that (8.55%) reported by the 3 019 first-time offenders (χ2 = 67.34, P < 0.001). Compared to those without craniocerebral trauma history, the participants with craniocerebral trauma history were at an increased risk of recidivism (unadjusted odds ratio [OR] = 1.87, 95% confidence interval [95%CI]: 1.61 - 2.18) and the risk remained significantly higher (OR = 1.51, 95%CI: 1.28 - 1.78) after adjusting for age, sex, marital status, residence region, education level, family type, self-reported economic status, and parental education level. ConclusionThe study found a significant association of craniocerebral trauma with increased risk of recidivism. The result highlights the importance of early detection, treatment, and intervention, as well as routine screening and rehabilitation of craniocerebral trauma, in preventing re-offending among prisoners and detainees.